The IMF's Communication Strategy. (Policy Papers; Policy Paper ;, 2007)
The strategy proposed in this paper seeks to build understanding and support for the IMF's reform agenda as outlined in the IMF's Medium-Term Strategy, further integrate communications with operations, raise the impact of communication tools, and rebalance outreach efforts.